THEORETICAL PRINCIPLES OF INFLUENCE OF THE LAW OF DIFFERENTIATED OPTIMUM ON THE EFFECTIVENESS OF THE ORGANIZATION - Дем’яненко, Сергій (SWorldJournal, 2022)
The theoretical aspects of connection of the law of differentiated optimum with the effectiveness of the organization are investigated. The essence of the law of differentiated optimum and its impact on the organization's profit through the dynamics of pr